Forbryder vs. offer - Beth Grothe Nielsen (Nordisk Tidsskrift for Kriminalvidenskab)
Taking its point of departure in Vagn Greve's contention (1972) that everybody is a criminal but only a certain group of people are punished and Greve's proposal that the explanation may be found in the relationship between offender and victim, this article looks into that relationship.